Analisis Dinamika Sosial Bagi Organisasi Serikat Pekerja pada Kebijakan Undang-Undang Cipta Kerja Peraturan Pemerintah Nomor 51 dalam Penetapan Upah Minimum 2024 di Provinsi Banten - Saepulloh, Asep; Dewi, Intan Indria; Masriyadi, Masriyadi; Laksana, April; Ferdiana , Riska (PANDITA: Interdisciplinary Journal of Public Affairs, 2024)
The annual minimum wage increase determined by the government is believed to be a complex calculation designed to meet the minimum needs of workers. However, with the introduction of a new policy formula in Government Regulation No. 51, where the alpha symbol (a) mentioned in paragraph 5 is a variable ranging from 0.10 to 0.30, the resulting percentage may be insignificant. This research aims to assess the impact of the percentage results obtained from Government Regulation No. 51 of 2023. The research method employed is descriptive analysis, utilizing both empirical and qualitative juridical study approaches. The discussion results reveal significant differences in the Minimum Wage decisions set by the Governor of Banten for the year 2024 compared to the calculated Minimum Wage increase in 2023. The percentage difference is not easily comparable due to the distinct references used for the increases in 2023 and 2024 – the difference in reference being between Minister of Manpower Regulation No. 18 of 2022 and Government Regulation No. 51, which yields significantly different percentage increases. The expected percentage through the discretion of the Regent, recommending 7.08%, contrasts sharply with the approved 1.51%, in accordance with the alpha index (a) calculation in Government Regulation No. 51